Lexical bundles in linguistics textbooks - Lee, Hye Kyung (Linguistic Research, 2020)
Lee, Hye-Kyung. Lexical bundles in linguistics textbooks. Linguistic Research 37(1), 121-145. In an attempt to help students in linguistics enhance their reading proficiency, this study identifies a total of 274 three-and four-word lexical bundles drawing on a 1.14-million-word corpus of linguistics textbooks. These bundles were first investigated in terms of their structural properties. Results of the structural analysis showed that NP-based and PP-based bundles accounted for almost 80 % of all bundles, consistent with previous studies showing that professional academic writing contained more intensive use of NPs than student writing (both native and non-native). Functional taxonomy of lexical bundles indicated that a high proportion of lexical bundles had referential functions (84.9%), whereas much less of them were discourse organizers (8.6%) and stance expressions (6.5%). Results of the present study add corroborative evidence to those of previous studies. The current study also produces a few findings regarding subject relatedness of yielded lexical bundles, the use of colloquial expressions (i.e., a lot of or pronoun-framed bundles), a higher frequency of passive constructions, and a notable number of tokens of the bundle around the world. Pedagogical implications of these findings are also suggested. (Ajou University).
Keywords: Academic discourse; Discipline-specificity; Lexical bundles; Linguistics textbooks; Subject relatedness